Development of a bilingual interdisciplinary scale assessing self-efficacy for participating in Medical Assistance in Dying - Tapp, Diane; Plaisance, Ariane; Boudreault, Nathalie; St-Pierre, Isabelle; Desbiens, Jean-Francois; Poitras, Sarah-Caroline; Lemay, Elizabeth; Urrea, Luis Alejandro; Lapointe, Amélie; Henry, Melissa; et al. (Canadian Medical Education Journal, 2023)
Medical Assistance in Dying (MAiD) is a complex process involving the person seeking care and their relatives. MAiD involves physical, psychosocial and spiritual needs, and consequently the involvement of an interdisciplinary team is beneficial. Therefore, updating the knowledge and skills of healthcare and social services professionals is critical. An interdisciplinary team from Laval University (Quebec, Canada) has developed a continuous training program for all health care and social services professionals who could be involved in the care of persons who request MAiD and their loved ones. It is crucial to assess whether the objectives of the continuous training program are being met, especially since this new training addresses several complex issues (legal, ethical, and clinical). Bandura's self-efficacy theory has been widely used to develop scales for assessing the impact of training programs and identifying knowledge gaps. Bandura's theory states that feeling secure in one's self-efficacy leads to self-determined motivation. Although there are various scales intended to measure self-efficacy in palliative care, none include self-efficacy for participating in the process surrounding MAiD. As a result, we aim to create a bilingual (English-French) interdisciplinary scale to assess self-efficacy for participating in the process surrounding MAiD. The scale will allow decision-makers and researchers to identify current knowledge gaps. It will also be useful for assessing the impact of current and future training programs addressing this end-of-life practice. In this work in progress, we briefly introduce the training program and the future steps in the development and validation of the scale.